2021
DOI: 10.1371/journal.pone.0248331
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid anxiety and depression: Prevalence and associated factors among pregnant women in Arba Minch zuria district, Gamo zone, southern Ethiopia

Abstract: Introduction Prenatal anxiety and depression are major health problems all over the world. The negative sequela of prenatal comorbid anxiety and depression (CAD) has been suggested to be higher than that of anxiety or depression alone. CAD increases the odds of preterm birth, low birth weight, prolonged labor, operative deliveries, postpartum psychiatric disorders and long term cognitive impairment for the newborn. Despite its significant ill consequences, there is a dearth of studies in low-and middle-income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 51 publications
(78 reference statements)
3
32
4
Order By: Relevance
“…The finding of the current study was relatively higher than previous studies conducted in Ethiopia during the COVID-19 pandemic (32.2%) (9), Nigeria (37.5%) (28), and China (36.77%) (29). The finding is significantly higher than studies from the Southern Ethiopia (10.04%) (26), South Africa (23%) (18), Tanzanian (25%) (30), China (6.8%) (31), and (11.18%) (27), Pakistan (20.4%) (32), Iran (21%) (15), Brazil (26.8%) (19), and Indonesia (29%) (33). On the other hand, the finding of the current study was lower than studies in Taiwan (52.1%) (34), India (55.7%) (35), Canada (57%) (8), and Turkey (64.5%) (36).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The finding of the current study was relatively higher than previous studies conducted in Ethiopia during the COVID-19 pandemic (32.2%) (9), Nigeria (37.5%) (28), and China (36.77%) (29). The finding is significantly higher than studies from the Southern Ethiopia (10.04%) (26), South Africa (23%) (18), Tanzanian (25%) (30), China (6.8%) (31), and (11.18%) (27), Pakistan (20.4%) (32), Iran (21%) (15), Brazil (26.8%) (19), and Indonesia (29%) (33). On the other hand, the finding of the current study was lower than studies in Taiwan (52.1%) (34), India (55.7%) (35), Canada (57%) (8), and Turkey (64.5%) (36).…”
Section: Discussioncontrasting
confidence: 85%
“…The current study reported that 43.7% of pregnant women experienced GAD during the COVID pandemic. The finding is higher than a study in Ethiopia (10.4%) done before the COVID-19 pandemic era ( 26 ). This is due to the unique stressor COVID-19 pandemic ( 8 ) is associated with an increased prevalence of anxiety in pregnant women during the pandemic ( 16 ).…”
Section: Discussioncontrasting
confidence: 70%
“…This is supported by a previous study [ 17 ], which reported that peoples with chronic illness have a higher likelihood of experiencing anxiety disorder than others. Moreover, another study reported that chronic illness had a significant effect on comorbid anxiety disorder [ 58 ]. Literature supported that having a chronic illness, as well as misusing addictive substances, can increase the likelihood of developing an anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A HFIAS rating levels a range from 0 to 27. In this study, household food security status categorized into two as “food secure” when the individual didn’t experience food inaccessibility conditions in the past 4 weeks and “food insecure” when individuals had unable to access enough food for necessary day to day activities [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fast Alcohol Screening Test (FAST) scale derived from the Alcohol Use Disorders Identification Test (AUDIT) by Hodgson et al, 2002.; was used to measure harmful drinking, FAST has 4 items with a rating score from a range of 0 to 16, where in a rating of > 3 shows harmful drinking [ 30 , 33 ].…”
Section: Methodsmentioning
confidence: 99%